APPLICATION OF WATER-BASED WEB-BASED MOBILE USING DIJKSTRA ALGORITHM - IKA, SUKIRNO; HANDAYANI UN, S.Kom., M.Kom., DEWI (Information Technology and Telematics, 2018)
Abstract - Tourism is the hallmark of an area. Each region and city has a tourist attraction that is seeded as his trademark. Such as district of Pati district which is located in Central Java province. The existence of this tourism can increase foreign exchange or income Government of Pati Regency. Therefore, the Government of Pati Regency through Tourism and Culture Office of Pati Regency has bridged the tourism sector. The purpose of this study is to assist travelers in determining the shortest route using Dijkstra's Algorithm. Mobile Application Design Star Web-Based Mobile Using DIJKSTRA Algorithm is created by using tools such as Sublime, PHP, Xampp, Bootstrap, Android Studio. Results of Application of Mobile Web Based Starch Using the DIJKSTRA Algorithm that can be downloaded tours on the playstore. With this application, tourists can find out the shortest route that can be taken from and to a tourist place in want in Pati Regency.. Keywords: DIJKSTRA Algorithm, Tour Application, Shortest Route. Abstrak - Pariwisata adalah merupakan ciri khas dari suatu daerah. Tiap daerah maupun kota memiliki objek pariwisata yang diunggulkan sebagai ciri khasnya. Seperti halnya kabupaten Pati yang terletak diprovinsi Jawa Tengah. Keberadaan pariwisata ini dapat menambah devisa atau pendapatan Pemerintah Kabupaten Pati. Oleh karena itu Pemerintah Kabupaten Pati melalui Dinas Pariwisata dan Kebudayaan Kabupaten Pati telah berupaya mengembangkan sektor pariwisata. Tujuan penelitian ini adalah untuk membantu wisatawan dalam menentukan rute terpendek menggunakan Algoritma Dijkstra.  Perancangan Aplikasi Wisata Pati Berbasis Web Mobile Dengan Menggunakan Algoritma DIJKSTRA ini dibuat dengan menggunakan tools seperti Sublime, PHP, Xampp, Bootstrap, Android Studio.        Hasil Aplikasi Wisata Pati Berbasis Web Mobile Dengan Menggunakan Algoritma DIJKSTRA yang dapat di unduh wisata di playstore. Dengan aplikasi ini wisatawan dapat mengetahui rute terpendek yang bisa di tempuh dari dan menuju suatu tempat wisata yang di inginkan di Kabupaten Pati. Kata Kunci : Algoritma DIJKSTRA, Aplikasi Wisata, Rute Terpendek.